The Effect of Steel Over Strength Ratio on Structure Behavior - Luthfian Ahmad; Mudiono Kasmuri (Recent in Engineering Science and Technology, 2024)
Seismic design of steel building structures according to SNI 7860:2020 determining the necessary strength of structural members based on the expected yield stress, Ry.Fy, and the expected tensile stress, Rt.Fu. However, the values of Ry and Rt in SNI 7860:2020 are not yet based on the testing of steel products in Indonesia and are still based on the provisions in AISC 341-16. This research was conducted by collecting data on steel tensile test results to obtain the over-strength ratio and then modeling the steel frame building using the over-strength steel provisions of SNI 7860:2020 and based on the tensile test results to determine the difference in structural behavior. Based on the tensile test results, WF300 steel has a yield strength ratio (Ry) of 1.78, which is higher than the SNI specification of 1.5, and a tensile strength ratio (Rt) of 1.35, which is higher than the SNI specification of 1.2. Based on pushover analysis, the deviation value at the initial formation of the plastic hinge on Structure A1 (Ry=1.5) in the x-axis direction of 79.352 mm is smaller than Structure B1 (Ry=1.78) by 94.01 mm. This indicates that the plastic hinge of Structure A1 is formed earlier than Structure B1.